(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study explores the innovative integration of transformable furniture and minimalist design in contemporary interior spaces. Despite the growing demand for space-saving and adaptable furniture, a knowledge gap persists regarding its practical implementation in urban residential settings. Using a mixed-methods approach, including design analysis and user feedback, the study investigates the functionality and aesthetic value of transformable furniture. Findings reveal that such designs significantly enhance spatial utility, reduce costs, and improve user satisfaction in minimalist interiors. These results underscore the potential of transformable furniture as a sustainable and efficient solution for modern living, with implications for designers and manufacturers in addressing urban housing challenges.